Transformational Leadership and Turnover Intention in the Digital Era: Sequential Mediation of LMX and Affective organizational Commitment. - Ines BOUSSEDRA (African Scientific Journal, 2025)
Abstract In a context of accelerated digital transformation, African organizations face major challenges in retaining talent. While transformational leadership (TL) is recognized for its positive effects on employee performance and engagement, the mechanisms by which it influences turnover intentions remain largely unexplored in digital and culturally specific environments. This research aims to fill this gap by proposing a sequential mediation model linking transformational leadership (TL), leader-member exchange (LMX) quality, affective organizational commitment (EA), and turnover intention (IL). By drawing on self-determination theory, social exchange theory, and LMX theory, the study offers an integrated reading of the motivational and relational dynamics specific to Tunisian organizations undergoing digitalization. Using a quantitative approach, data were collected from 147 Tunisian employees and then analyzed using Hayes' (2018) macro PROCESS model 6 in SPSS. The results reveal partial mediation, mainly driven by affective commitment, while the quality of the leader-member relationship does not have a significant direct mediating effect. The sequential path via LMX and EA is marginally significant. These results enrich the literature on human resource management and offer concrete avenues for strengthening talent retention in changing organizations. Managerial and theoretical implications are discussed, as well as future research prospects. Keywords: transformational leadership – LMX – affective organizational commitment – turnover intention– digital transformation. Résumé Dans un environnement de transformation digitale accélérée, les organisations africaines sont confrontées à des défis majeurs en matière de fidélisation des talents. Bien que, le leadership transformationnel (LT) est reconnu pour ses effets positifs sur la performance et l’engagement des collaborateurs, les mécanismes par lesquels il influence l’intention de quitter restent encore peu explorés dans les environnements digitales et culturellement spécifiques. Cette recherche vise à réduire le fossé en proposant un modèle de médiation séquentielle articulant le leadership transformationnel, la qualité de la relation leader–membre (LMX), l’engagement organisationnel affectif et l’intention de quitter. En mobilisant les apports de la théorie de l’autodétermination, de l’échange social et du LMX, l’étude offre une lecture intégrée des dynamiques motivationnelles et relationnelles liée aux organisations tunisiennes en phase de digitalisation. En suivant une approche quantitative, les données ont été recueillies auprès de 147 employés tunisiens, analysées, par la suite, à l’aide du modèle 6 du macro PROCESS de Hayes (2018) sous SPSS. Les résultats révèlent une médiation partielle, principalement portée par l’engagement affectif, tandis que la qualité de la relation leader–membre n’exerce pas d’effet médiateur direct significatif. Le chemin séquentiel via LMX et engagement affectif est marginalement significatif. Ces résultats embellissent la littérature sur le management des ressources humaines et proposent des pistes concrètes pour renforcer la rétention des talents dans les organisations en pleine mutation. Des implications managériales et théoriques sont discutées, ainsi que des perspectives de recherche futures. Mots clés : leadership transformationnel – LMX – engagement organisationnel affectif– intention de quitter –transformation digitale.